Art. IX.—The O'mánee Dialect of Arabic - Jayakar, A. S. G. (The Journal of the Royal Asiatic Society of Great Britain and Ireland, 1889)
Keywords: Linguistique -- Oman

Art. XI.—The O'mánee Dialect of Arabic - Jayakar, A. S. G. (Journal of the Royal Asiatic Society, 1889)
In compiling the following vocabulary of 'Omanee words, the principal aim has been to give only such words as exhibit the dialectical peculiarities mentioned in the preceding Part, and not to furnish a complete list of words in common use in O'mán. Technical words, or words employed in agriculture, trade, arts, manufactures, etc., have been intentionally omitted, as they would be beyond the scope and extent of the present paper. Most of the words, it will be seen, are of Arabic origin, and the dialectical sense, wherever it differs from the original, is either metaphorical or an extension of the sense conveyed by the original root.
Keywords: Linguistique -- Oman